Inequality, poverty and food insecurity in the south, south-eastern and gulf of mexico regions, 2008-2018 - Espinosa Cortés, Luz María (2022)
Since the eighties of last century, economic neoliberalism has dismantled the social state and governments have oriented their social policy towards targeting extreme poverty in order to reduce public expenditure. The purpose of this article is to present CONEVAL estimations regarding extreme poverty and food insecurity (FI) between 2008 and 2020, and to discuss the relevance of other methods to determine these figures. Official records from eight federal states grouped in three regions of the country, were analyzed. In 2018, the CONEVAL statistics showed a reduction in extreme poverty and an increase in moderate poverty in all states but Yucatan state (south-east). In 2020, extreme poverty and FI only has diminished in the south. When using official data, extreme poverty is underestimated, therefore, we discuss the need to review and adjust poverty measurement thresholds constantly because they are mobile and change over time. In conclusion, with the change from a subsidizing state to a welfare state, a re-evaluation of the official thresholds used in the poverty measurement is necessary.